Cyclic dinucleotides mediate bacterial immunity by dinucleotide cyclase in Vibrio - Lu, Zengzeng; Fu, Yuqian; Zhou, Xueyuan; Du, Hekang; Chen, Qi (Frontiers in Microbiology, 2022)
The cyclic GMP-AMP (cGAMP) synthase (cGAS) recognizes cytosolic DNA and synthesizes the second messenger, cGAMP, thus activating the adaptor protein stimulator of interferon genes (STING) and initiating the innate immune responses against microbial infections. cGAS-STING pathway has been crucially implicated in autoimmune diseases, cellular senescence, and cancer immunotherapy, while the cGAS-like receptors in bacteria can protect it against viral infections. DncV is a dinucleotide cyclase originally identified in Vibrio cholerae. The synthesis of cyclic nucleotides by DncV, including c-di-GMP, c-di-AMP, and cGAMP mediates bacterial colonization, cell membrane formation, and virulence. DncV is a structural and functional homolog of the mammalian cytoplasmic DNA sensor, cGAS, implicating cGAS-STING signaling cascades may have originated in the bacterial immune system. Herein, we summarize the roles of DncV in bacterial immunity, which are expected to provide insights into the evolution of cGAS-STING signaling.